Studying the Effect ofthe Type of Dirt onthe Electric Performance of Polycrystalline Silicon Photovoltaic Panels (Damascus University Journal for engineering sciences, 2025)
The difference in the location of installation of the photovoltaic panelsis accompanied by a change in their performance, as it was noticed that theperformance of the same photovoltaic panels of the same manufacture, the same manufacturing date, and the same model gives different performance according to the place of installation, at the same climatic parameters of solar radiation and working temperature. Therefore, this study aims to demonstrate the effect of the type of dirt that can cover the front surface of a polycrystalline photovoltaic panel on its performance by applying different materials from building sand to cement to marine sand to red sand to simulate different installation locations, and to indicate which one has the most impact on the output of this panel, where it has shown that black cement has the most impact, as the power decreases from clean by about 53%, while construction sand about 26.8%, while marine sand and red agricultural sand were the least affected by about 2.5% and 0.5%.
Keywords: poly crystals photovoltaic panels; front surface; dirt; panel power